A comparison of measles-rubella-zoster reaction, oligoclonal IgG bands, oligoclonal kappa free light chains and kappa index in multiple sclerosis - Zondra Revendova, Kamila; Svub, Krystof; Bunganic, Radovan; Pelisek, Ondrej; Volny, Ondrej; Ganesh, Aravind; Bar, Michal; Zeman, David; Kusnierova, Pavlina (Multiple sclerosis and related disorders, 2024)
BACKGROUND AND OBJECTIVES: To evaluate the diagnostic performance of the measles-rubella-zoster reaction (MRZR) in a large real-world multiple sclerosis (MS) cohort. Second, to compare MRZR with the determination of oligoclonal IgG bands (OCB), oligoclonal kappa free light chain bands (oKFLC), and the KFLC index. METHODS: A single-center retrospective study was conducted at the University Hospital Ostrava (Czech Republic). Patients were eligible if aged ≥18 years with a determined clinical diagnosis. IgG antibodies against measles (M), rubella (R), and varicella zoster (Z) viruses were determined in paired CSF and serum using ELISA and MRZR indicated as positive if at least two components had an antibody index >1.4. OCB and oKFLC were detected by means of isoelectric focusing, and KFLC CSF and serum concentrations for calculation of the KFLC index were determined immunochemically. RESULTS: A total of 1,751 patients were included in the analyzed data set, which comprised 379 MS patients and 1,372 non-MS controls. The frequency of positive MRZR was higher in MS than in non-MS cases (MS 32.2 % vs non-MS 2.8 %; p < 0.001). This corresponded to a specificity of 97.2 % (95 % CI 96.1-98.0) and sensitivity of 32.2 % (95 % CI 27.5-37.2) and overall accuracy of 83.1 % (95 % CI 81.3-84.8). In comparison, the highest sensitivity of 95.6% (95 % CI 93.0-97.5) was for OCB with specificity of 86.9 % (95 % CI 84.9-88.7), followed by oKFLC with sensitivity and specificity of 94.7 % (95 % CI 91.5-96.9) and 78.4% (95 % CI 75.7-80.8), respectively, and the KFLC index with sensitivity of 92.5 % (95 % CI 86.6-96.3) and specificity of 93.5 % (95 % CI 90.5-95.9). DISCUSSION: MRZR remains a very specific test for the diagnosis of MS but has low sensitivity, which disallows its independent use. In contrast, OCB showed the highest sensitivity and thus remains the gold standard for the diagnosis of MS.
Keywords: spalničky; Oligoclonal IgG bands; MRZ reaction; imunoglobulin G; Retrospective Studies; roztroušená skleróza; mladiství; oligoklonální proužky; Adult; Herpes Zoster; Kappa index; Multiple Sclerosis; Immunoglobulin G; Immunoglobulin kappa-Chains; herpes zoster; Oligoclonal kappa free light chains; retrospektivní studie; Humans; Oligoclonal Bands; zarděnky; biologické markery; Multiple sclerosis; Rubella; imunoglobuliny - kappa-řetězce; Measles; dospělí; Biomarkers; Adolescent; lidé